Injury to the Premature Cerebellum: Outcome is Related to Remote Cortical Development. (11th November 2012) - Limperopoulos, Catherine; Chilingaryan, Gevorg; Sullivan, Nancy; Guizard, Nicolas; Robertson, Richard L.; du Plessis, Adré J.
Abstract : Cerebellar injury is an important complication of preterm birth with far-reaching neuropsychiatric sequelae. We have previously shown a significant association between isolated injury to the premature cerebellum and subsequent impairment of regional volumetric growth in the contralateral cerebrum. In the current study, we examine the relationship between these remote regional impairments of cerebral volumetric growth and domain-specific functional deficits in these children. In 40 ex-preterm infants with isolated cerebellar injury, we performed neurodevelopmental evaluations and quantitative magnetic resonance imaging (MRI) studies at a mean age of 34 months. We measured cortical gray matter volumes in 8 parcellated regions of each cerebral hemisphere, as well as right and left cerebellar volumes. We show highly significant associations between early signs of autism and dorsolateral prefrontal cortex volume ( P < 0.001); gross motor scores and sensorimotor cortical volumes ( P < 0.001); and cognitive and expressive language scores and premotor and mid-temporal cortical volumes ( P < 0.001). By multivariate analyses, each unit increase in the corresponding regional cerebral volume was associated with lower odds of abnormal outcome score, adjusted for age at MRI and contralateral cerebellar volume. This is the first report linking secondary impairment of remote cerebral cortical growth and functional disabilities in survivors of prematurity-related cerebellar brain injury.